Health guidelines for the use of wastewater in agriculture and aquaculture : report of a WHO scientific group, meeting held in Geneva from 18 to 23 November 1987 - WHO Scientific Group on Health Aspects of Use of Treated Wastewater for Agriculture and Aquaculture; World Health Organization (Geneva : World Health Organization, 1989)
Issues revised technical and practical guidelines for the use of wastewater in agricultural irrigation, greenspace watering, and fish production in accordance with measures that protect the environment and safeguard against the transmission of disease. Representing the consensus reached by an international group of experts, the book introduces an approach to wastewater use that is at once less restrictive than previous guidelines and more realistic in terms of documented risks to health. Throughout, an effort is made to give water resource managers the evidence, quality indicators, and technical advice needed to exploit this valuable resource without endangering public health. The book opens with a brief review of the origins of previous guidelines, experiences with their use, and reasons why their quality standards are now regarded as too restrictive in terms of bacterial indicators and inadequate in terms of their failure to protect against the major risk of helminth infections. The most extensive part of the book focuses on health problems and measures for protection. Tables, diagrams and charts help document specific problems in terms of the characteristics and environmental behaviour of excreted pathogens, survival times for pathogens in soil and on crops, measures of health risks, including the epidemiological concept of actual or attributable risk, and factors influencing the degree to which a potential risk posed by a pathogen can become an actual risk of disease transmission. Against this background, the book issues detailed effluent microbiological quality guidelines for agriculture, gives tentative guidelines for aquaculture, and outlines a series of health protection measures.
1. Introduction -- 2. Background -- 3. Scope of the report -- 4. Major aspects of wastewater reuse -- 5. Current practice in wastewater reuse -- 6. Health aspects of wastewater reuse -- 7. Health protection measures in wastewater reuse -- 8. Planning and implementing health safeguards -- 9. research needs related to health protection -- 10.Conclusions and recommendations -- Acknowledgements -- references -- Annexes
Keywords: Sewage; Water Microbiology; Soil Microbiology; Water Supply and Sanitation